Gatekeeper training for vendors to reduce pesticide self-poisoning in rural South Asia: a study protocol for a stepped-wedge cluster randomised controlled trial. Issue 4 (4th April 2022) - Weerasinghe, Manjula; Pearson, Melissa; Turner, Nicholas; Metcalfe, Chris; Gunnell, David J; Agampodi, Suneth; Hawton, Keith; Agampodi, Thilini; Miller, Matthew; Jayamanne, Shaluka; Parker, Simon; Sumith, Jayakody Arachchige; et al.
Abstract : Introduction: Pesticide self-poisoning kills an estimated 110 000–168 000 people worldwide annually. Data from South Asia indicate that in 15%–20% of attempted suicides and 30%–50% of completed suicides involving pesticides these are purchased shortly beforehand for this purpose. Individuals who are intoxicated with alcohol and/or non-farmers represent 72% of such customers. We have developed a 'gatekeeper' training programme for vendors to enable them to identify individuals at high risk of self-poisoning (gatekeeper function) and prevent such individuals from accessing pesticides (means restriction). The primary aim of the study is to evaluate the effectiveness of the gatekeeper intervention in preventing pesticide self-poisoning in Sri Lanka. Other aims are to identify method substitution and to assess the cost and cost-effectiveness of the intervention. Methods and analysis: A stepped-wedge cluster randomised trial of a gatekeeper intervention is being conducted in rural Sri Lanka with a population of approximately 2.7 million. The gatekeeper intervention is being introduced into 70 administrative divisions in random order at each of 30 steps over a 40-month period. The primary outcome is the number of pesticide self-poisoning cases identified from surveillance of hospitals and police stations. Secondary outcomes include: number of self-poisoning cases using pesticides purchased within the previous 24 hours, total number of all forms of self-harm and suicides. Intervention effectiveness will be estimated by comparing outcome measures between the pretraining and post-training periods across the divisions in the study area. The original study protocol has been adapted as necessary in light of the impact of the COVID-19. Ethics and dissemination: The Ethical Review Committee of the Faculty of Medicine and Allied Sciences, Rajarata University, Sri Lanka (ERC/2018/30), and the ACCORD Medical Research Ethics Committee, Edinburgh University (18-HV-053) approved the study. Results will be disseminated in scientific peer-reviewed journals. Trial registration number: SLCTR/2019/006, U1111-1220-8046.